A case of generalized acute cutaneous lupus erythematosus - Yun ZHAO; Jianqin LI; Shiping ZHAN; Qianwen FAN; Yonghua TONG; Changzheng HUANG (Pifu-xingbing zhenliaoxue zazhi, 2024)
A case of acute cutaneous lupus erythematosus is reported. A 75-year-old male presented with asymptomatic erythema on both the ears and face for over a month. Dermatological examination showed fused erythema on both sides of the face and ears. Multiple erythema, maculae and red papules in different sizes were seen on the back, and some lesions were accompanied with scales. Under a dermoscope, there were perifollicular white halos and amorphous areas with scales on red background. Histopathological examination of facial skin lesions showed epidermal atrophy and liquefaction degeneration of the basal cells, and perivascular infiltration of lymphocytes in the superficial and middle dermis. Alcian blue staining was focally positive in the dermis. Diagnosis: generalized acute cutaneous lupus erythematosus. Satisfactory results were achieved after oral administration of hydroxychloroquine combined with methylprednisolone tablets. No recurrence was observed during follow-up.